Psychological outcomes of family caregivers of mental illness patients - Mohamad, Mohd Suhaimi; Subhi, Nasrudin; Jusoff, Kamaruzaman; Wan Jaafar, Wan Azreena; Chong, Sheau Tsuey; Ibrahim, Fauziah; Mohamad, Lukman @ Zawawi; Sarnon @ Kusenin, Norulhuda; Nen, Salina; Mohd Hoesni, Suzana; Alavi, Khadijah (IDOSI Publications, 2011)
Previous research shows considerable variability in the impact of caring on family caregivers of mental illness but the multidimensional experience of caring remains unexplained. The study aimed to identify family experiences of caring in a developing country. There were 154 family caregivers recruited for the survey. In addition, twenty-four respondents participated in semi-structured interviews about their personal caring experiences. This study found that majority of caregivers was women and aged less than 60 years. More than half of the participants were found to be psychologically distressed. Consistent with the stress-coping model, only caregivers' negative appraisal was a strong predictor of psychological distress and accounted for a substantial proportion of its variance. Positive appraisal, ethnicity and residential area did not predict psychological distress. Interview findings related to the coping styles and social supports of the family caregivers. The implications for mental health services are that many of the caregivers need help in their own right. Not only the person with mental illness who should be targeted for evaluation but the differences in caregivers' appraisal on their caring role taken into consideration.